Preparation and characterization of Pistacia atlantica oleo-gum-resin-loaded electrospun nanofibers and evaluating its wound healing activity in two rat models of skin scar and burn wound - Mohammadi, Ghobad; Safari, Mosayyeb; Karimi, Masoud; Iranpanah, Amin; Farzaei, Mohammad Hosein; Fakhri, Sajad; Echeverría, Javier (Frontiers in Pharmacology, 2024)
Background: One of the proceedings being taken today in wound healing research is to identify promising biological materials that not only heal wounds but also vanish scarring. The effectiveness of nanofibers like polyvinyl alcohol (PVA), in improving wound healing can be related to their unique properties. Pistacia atlantica Desf. subsp. kurdica (Zohary) Rech. f. (PAK) [Anacardiaceae] is one of the most effective herbal remedies for the treatment of different diseases like skin injuries due to its numerous pharmacological and biological properties, including anti-inflammatory, antioxidant, and anti-bacterial effects. Purpose: Our study aimed to evaluate the wound-healing activity of nanofibers containing PVA/PAK oleo-gum-resin in two rat burn and excision wound repair models. Material and methods: PVA/PKA nanofibers were prepared using the electrospinning method. Scanning electron microscope (SEM) images and mechanical properties of nanofibers were explored. Diffusion and releasing experiments of nanofibers were performed by the UV visible method at different time intervals and up to 72 hours. The animal models were induced by excision and burn in Wistar rat's skin and the wound surface area was measured during the experiment for 10 and 21 days, respectively. On the last day, the wound tissue was removed for histological studies, and serum oxidative factors were measured to evaluate the antioxidant properties of the PVA/PKA. Results and discussion: The mechanical properties of PVA/PKA nanofibers showed that the presence of gum increased the tensile strength and decreased the tensile strength of the fibers simultaneously. In vivo results showed that PVA/PKA nanofibers led to a significant reduction in wound size and tissue damage and negative control groups. Wound contraction was higher in rats treated with PVA/PKA nanofibers. Additionally, antioxidative serum levels of catalase and glutathione were higher in the PVA/PKA nanofiber groups even in comparison to positive control groups. Conclusion: Pistacia atlantica oleo-gum-resin-loaded electrospun nanofibers potentially improve excision and burn models of skin scars in rats through antioxidative and tissue regeneration mechanisms.